Physical inactivity and associated factors in adults, São Paulo, Brazil - Zanchetta, Luane Margarete; Barros, Marilisa Berti de Azevedo; César, Chester Luiz Galvão; Carandina, Luana [UNESP]; Goldbaum, Moisés; Alves, Maria Cecília Goi Porto (My University, 2010)
Objective: To analyze the prevalence of overall and leisure time physical inactivity and associated factors and types of exercises or sports modalities according to schooling in 2,050 adults from 18 to 59 years of age - state of São Paulo, Brazil. Methods: Population-based cross-sectional study with a stratified sample of clusters performed in multiple stages. Physical inactivity was determined using the short version of the International Physical Activity Questionnaire - IPAQ and by a question on the regular practice of leisure time physical activity. Data analysis took the sample design into account. Results: Prevalence of physical inactivity during leisure was higher among women. Poisson multiple regression model in man indicated that overall sedentarism was lower among single and separated men, students and without car in the household. Leisure physical inactivity was greater among men over forty years, among those with less schooling and full-time students. Overall physical inactivity was more prevalent among woman with more schooling, with less qualified occupations and widows. Leisure physical inactivity decreased with age and schooling. Among modalities practiced for leisure, walking was more prevalent among women and football was more prevalent among men. Most modalities were directly associated with schooling; approximately 25% of the individuals with more than 12 years of schooling practiced walking. Conclusions: These results suggest that interventions and public policies to promote physical activity should consider differences in gender and socioeconomic status as well as the preferences for different modalities and the context in which the physical activity is practiced.
Inatividade física e fatores associados em adultos, São Paulo, Brasil
Keywords: Brazil; Exercise; Health Surveys; Leisure Activities; Physical activity; Risk Factors